Cerebellar parcellation in schizophrenia and bipolar disorder. (25th October 2019) - Laidi, C.; Hajek, T.; Spaniel, F.; Kolenic, M.; d'Albis, M.‐A.; Sarrazin, S.; Mangin, J.‐F.; Duchesnay, E.; Brambilla, P.; Wessa, M.; Linke, J.; Polosan, M.; et al.
Abstract : Objective: The cerebellum is involved in cognitive processing and emotion control. Cerebellar alterations could explain symptoms of schizophrenia spectrum disorder (SZ) and bipolar disorder (BD). In addition, literature suggests that lithium might influence cerebellar anatomy. Our aim was to study cerebellar anatomy in SZ and BD, and investigate the effect of lithium. Methods: Participants from 7 centers worldwide underwent a 3T MRI. We included 182 patients with SZ, 144 patients with BD, and 322 controls. We automatically segmented the cerebellum using the CERES pipeline. All outputs were visually inspected. Results: Patients with SZ showed a smaller global cerebellar gray matter volume compared to controls, with most of the changes located to the cognitive part of the cerebellum (Crus II and lobule VIIb). This decrease was present in the subgroup of patients with recent‐onset SZ. We did not find any alterations in the cerebellum in patients with BD. However, patients medicated with lithium had a larger size of the anterior cerebellum, compared to patients not treated with lithium. Conclusion: Our multicenter study supports a distinct pattern of cerebellar alterations in SZ and BD.